Optical Fiber Sensor Technology in Portugal - Lobo Ribeiro, Antonio B. (2019)
A general overview of the R&D activity in fiber optic sensing developed over the last fifteen years in Portugal is given. Different topics are addressed, including inter- ferometric, intensity and Bragg grating based fiber optic sensors, signal processing and multiplexing techniques, optical current sensors, together with some references to field trials and applications. Possible guidelines for present and future national R&D activity on this subject are outlined.